2018
DOI: 10.1021/acs.jcim.8b00216
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Molecular Overlays Derived from Three-Dimensional Hydrophobic Similarity with PharmScreen

Abstract: Molecular alignment is a standard procedure for three-dimensional (3D) similarity measurements and pharmacophore elucidation. This process is influenced by several factors, such as the physicochemical descriptors utilized to account for the molecular determinants of biological activity and the reference templates. Relying on the hypothesis that the maximal achievable binding affinity for a drug-like molecule is largely due to desolvation, we explore a novel strategy for 3D molecular overlays that exploits the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 72 publications
0
27
0
Order By: Relevance
“…Accordingly, the relationships between compounds in a given library and one or more known actives are examined by similarity measurements using suitable molecular descriptors. These measurements can be performed based on 1D and 2D descriptors, generally encoding information about the chemical nature of compounds and their topological features [ 25 , 26 , 27 ], and 3D descriptors associated to molecular fields [ 28 , 29 , 30 , 31 ], shape and volume [ 32 , 33 ], and pharmacophores [ 28 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the relationships between compounds in a given library and one or more known actives are examined by similarity measurements using suitable molecular descriptors. These measurements can be performed based on 1D and 2D descriptors, generally encoding information about the chemical nature of compounds and their topological features [ 25 , 26 , 27 ], and 3D descriptors associated to molecular fields [ 28 , 29 , 30 , 31 ], shape and volume [ 32 , 33 ], and pharmacophores [ 28 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Choice of this level of theory was motivated by its low computational cost compared to ab initio methods". 64 The authors compared the performances of MST/RM1 and MST/B3LYP to evaluate the effects of the method to calculate the hydrophobic contributions, having obtained similar results. In conclusion, the authors mentioned: "Therefore, these findings support the suitability of the semiempirical RM1 Hamiltonian, which offers a much better balance between overlay accuracy and computational expensiveness".…”
Section: Rm1 Improvementsmentioning
confidence: 95%
“…The RM1 UME for all lanthanides, now range from a minimum of 0.04 Å for Dy III , 39 Ho III39 and Er III39 to 0.08 Å for Ce III , 39 Yb III37 and Lu III trivalent ions. 37 Recently, Vázquez et al 64 reported a strategy for "3D molecular overlays that exploits the partitioning of molecular hydrophobicity into atomic contributions in conjunction with information about the distribution of hydrogen-bond (HB)". This method was implemented in the PharmScreen software, and the authors added the derivation of the fractional hydrophobic contributions that included a quantum mechanical version of the MST continuum model.…”
Section: Rm1 Improvementsmentioning
confidence: 99%
See 2 more Smart Citations